Clinical Experience of Professor Ma Shuanquan in Treating Androgenetic Alopecia - Fan, Lin; Wang, Liwen (Journal of Contemporary Medical Practice, 2024)
Professor Ma Shuanquan believes that the root cause of alopecia lies in the liver, spleen, and kidneys .Insufficient innate endowment, excessive contemplation, or liver and spleen damage, resulting in insufficient liver blood, spleen dysfunction, and Syndrome of deficiency of kidney essence, leads to blood stasis in the hair follicles, blocking the flow of qi and blood, and causing hair follicles to lose nourishment, resulting in androgenetic alopecia. In treatment, Professor Ma divides it into two types based on the differentiation of liver and kidney deficiency and spleen and kidney deficiency. The treatment methods include nourishing the liver and kidneys, tonifying the spleen and kidneys, blood circulation removing blood stasis, and qi-regulating and calming the mind Chinese medicines to achieve individualized treatment, with significant therapeutic effects.